STRUCTURE-BASED DRUG DESIGN METHOD: MOLECULAR DOCKING STUDY AND PHARMACOPHORE MODELLING OF APIGENIN AS AN ANTIMALARIAL - HERMANTO, FAIZAL; SYAM, AKHIRUL KAHFI; HAQ, FAHMY AHSANUL; RACHMAWAN, R. LUCKY (International Journal of Applied Pharmaceutics, 2023)
Objective: Uses molecular docking and pharmacophore modeling methods to examine the antimalarial activity of apigenin (API) on distinct kinds and varieties of P. falciparum (Pf) receptors. Methods: Using Autodock 4.0.1 and ligandscout software, molecular docking was conducted on multiple types of Pf receptors, including lactate dehydrogenase (Oxidoreductase), Enoyl-acyl carrier-protein (Oxidoreductase), Triose-phosphate (Isomerase), and plasmepsin II (Hydroxylase). Results: The lowest free energy binding values found in two of the four investigations (API on an enoyl-acyl carrier and triose-phosphate receptors) suggested a potential effect. These values were-8.06 kcal/mol and-8.76 kcal/mol, respectively. The API had lower values of the inhibitory constant on the lactate dehydrogenase, enoyl-acyl carrier-protein, Triose-phosphate, and plasmepsin II receptors (44.06 µM, 1.24 µM, 376.76 nM, and 57.04 µM, respectively). In terms of the essential elements of amino acid residue interaction, the API and the native ligand were identical (SER218 for 1LF3 receptor; LEU315, GLY110, and TYR111 for 1NWH receptor; VAL212, LYS12, ASN233, and GLY232 for 1O5X receptor; and ILE31, PRO250, and PRO246 for 1U4O receptor). According to the findings of the pharmacophore modeling, the functional groups of hydroxyl were the most important functional groups to interact with the important amino acid residues of the receptors. Conclusion: The API considerably displays competitive antimalarial potency in various Pf receptors.